The Potential for Office Automation in Department Stores - Kwo, T. T. (Management Science, 1965)
Potential for office automation in department stores is explored by sales volume class. This is done in terms of the present-day expenses in the clerical work area and the inventory management area typical of the stores in each volume class. Some characteristics of the “typical” stores are also briefly reviewed. The data used are those given in the Harvard Business School Survey conducted in 1963 [McNair, M. P. 1962. Operating Results of Department and Specialty Stores in 1962. Graduate School of Business Administration, Harvard University, Boston, Massachusetts.].